Corneal Epithelial Remodeling after LASIK Measured by Fourier-Domain Optical Coherence Tomography - Maolong Tang; Yan Li; David Huang (Journal of Ophthalmology)
Purpose. To quantify corneal epithelial thickness changes after myopic LASIK by OCT. Methods. Epithelial thickness before and after myopic LASIK were measured by a Fourier-domain OCT system. Average central (within 1 mm diameter) and paracentral epithelial thickness (5~6 mm diameter) before and after LASIK were compared. Correlation between central epithelial thickness change and laser spherical equivalent setting was evaluated. An epithelial smoothing constant was estimated based on a mathematical model published previously. Results. Nineteen eyes from 11 subjects were included in the study. Eyes had myopic LASIK ranging from −1.69 D to −6.75 D spherical equivalent. The average central epithelial thickness was 52.6 ± 4.1 μm before LASIK and 56.2 ± 4.3 μm 3 months after LASIK (p=0.002). The average paracentral epithelial thickness was 51.6 ± 6.6 μm before LASIK and 54.8 ± 4.3 μm 3 months after LASIK (p=0.007). The change in average central epithelial thickness was correlated with laser spherical equivalent (R2 = 0.40, p=0.028). The epithelial smoothing constant was estimated to be 0.46 mm. Conclusions. Corneal epithelial thickens centrally and paracentrally after myopic LASIK. The extent of epithelial remodeling correlated with the amount of LASIK correction and could be predicted by a mathematical model.